THE SOCIOPRAGMATIC DESCRIPTION OF SPEECH IN ENGLISH AND UZBEK DRAMA - Jo`rayeva Sabina, (TADQIQOTLAR, 2025)
Abstract: This article explores the sociopragmatic features of speech in English and Uzbek drama, focusing on how social norms, cultural expectations, and pragmatic conventions shape characters’ linguistic behavior. By analyzing selected plays from both  traditions,  the  study  investigates  speech  acts,  politeness  strategies,  forms  of address, turn-taking, and pragmatic implicatures, revealing how playwrights encode social roles, power relations, and interpersonal dynamics within dialogue. The research demonstrates  that  English  drama  often  employs  indirectness,  hedging,  and  subtle conversational  cues  to  reflect  individualism  and  social  hierarchy,  whereas  Uzbek drama emphasizes honorifics, culturally rooted expressions, and community-oriented communicative  practices,  reflecting  collectivist  values.  Through  a  comparative approach,  the  article  highlights  both  universal  and  culturally  specific  aspects  of dramatic speech, offering insights into the intersection of language, society, and literary art. The findings contribute to a deeper understanding of cross-cultural pragmatics, dramatic discourse analysis, and the role of sociocultural norms in shaping linguistic interaction in literature.